Features of intestinal microbiota composition in cancer patients - V. V. Aginova; Z. V. Grigorievskaya; I. N. Petukhova; N. S. Bagirova; I. V. Tereshchenko; I. V. Samoylenko; A. O. Kuzmenko; P. V. Kononets (Сибирский онкологический журнал, 2025)
Objective: to evaluate and compare the qualitative and quantitative composition of the intestinal microbiota in patients with malignant neoplasms of various localizations. Material and Methods. The study included patients who received different types of treatment in N.N. Blokhin Oncology Research Center, Moscow, Russia in 2023 for gastric cancer, including cardioesophageal adenocarcinoma (group 1), esophageal squamous cell carcinoma (group 2) and metastatic or locally advanced melanoma of the skin (group 3). All patients had to have morphologic verification of the diagnosis at the time of inclusion, be over 18 years old, have an ECOG performance status of ≤1, and have no evidence of intestinal infection, as well as not take antibiotics within 28 days prior to entry into the study. Stool samples were collected during patients’ hospitalization. The quantitative and qualitative composition of microorganisms of 17 taxonomic groups was evaluated. Microorganisms were cultured according to standard microbiological methods, taking into account the growth conditions of a particular group of microorganisms. Species identification of microbial isolates was obtained by matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF) and MALDI Biotyper v.3.0 software (Bruker daltonics, Germany). Descriptive statistics methods from the SPSS Statistics, v.27 software package were used. To quantitatively describe the species diversity of the gut microbiota, calculations were performed using the Margalef species richness index (d) and Shannon’s (H) diversity index. The criterion of uniformity of microbial species distribution according to their abundance in the population community was evaluated using the Pielow index (E). The Hutcheson’s T-criterion was used to test the significance of differences between sample sets of Shannon index values and to obtain statistically correct estimates of differences (p≤0.05). Results. A total of 63 samples of biological material (feces) were investigated. A change in the quantitative composition of intestinal microbiota in all study groups was found, which may have a negative impact on the general condition of the patient and the effectiveness of antitumor treatment. The increase in the proportion of Proteobacteria (Enterobacterales) can be considered as a risk factor for the development of infectious complications caused by Gram-negative microorganisms. The analysis of factors influencing the taxonomic diversity of intestinal microbiota revealed no significant differences in the composition of intestinal microbiota between the groups of patients with malignant tumors of different nosological forms (p>0.05).